Risk of Hepatitis B Virus Reactivation Among Patients Treated With Ledipasvir-Sofosbuvir for Hepatitis C Virus Infection. Issue 10 (November 2018) - Yanny, Beshoy T.; Latt, Nyan L.; Saab, Sammy; Han, Steven; Choi, Gina; Kramer, Jason; Sahota, Amandeep K.
Abstract : Background: Direct acting antiviral (DAA) agents are the standard of care for treatment of hepatitis C virus (HCV)–infected individuals. Hepatitis B virus (HBV) reactivation during HCV treatment has been reported, the incidence and clinical outcome remains unclear. The aim of our study is to examine the risk of HBV reactivation in actively infected or previously exposed patients during or after HCV treatment with DAAs. Methods: Adults with chronic HCV infection previously exposed or actively infected with HBV and treated with DAAs between December 2015 to 2016 were included. Electronic medical records were reviewed for HCV treatment dates, HCV treatment response, DAA used, HBV status, and concurrent HBV treatment. Primary end-point was to determine the risk of HBV reactivation during or up to 3 months after DAA treatment. Results: We identified 283 patients, and 100% of patients completed HCV treatment with ledipasvir-sofosbuvir. 93% had HCV genotype-1 of whom 91% achieved sustained viral response at 12 weeks posttreatment (SVR-12). In total, 7% had HCV genotype-4 who achieved SVR-12 of 84%. Mean (±SD) age was 59.7 (±7) years, and 58% were male. A total of 45% of patients had hepatitis B core antibody (HBcAb) positive and hepatitis B surface antigen (HBsAg) negative. In total, 55% of patients had a positive HBsAg before HCV DAA treatment. No HBV reactivation was encountered in the (HBcAb) positive HBsAg-negative cohort nor in the (HBsAg) positive group with 95% confidence interval (0-0.023) and (0-0.019), respectively. Conclusion: In our study of patients with HCV and isolated hepatitis B core or HBsAg positivity, no HCV patients treated with DAA experienced HBV reactivation.